Strengthening conflict sensitivity in Kenya’s county climate change fund: Kitui county - Medina, Leonardo; Schapendonk, Frans; Jaskolski, Martina; Osumba, Joab; Jebiwott, Alice; Mutuku, Munini; Takaindisa, Joyce; Giti, Daniel (2025)
This policy brief explores how Kitui County is applying Kenya’s County Climate Change Fund (CCCF) to foster conflict-sensitive climate adaptation. The study assesses whether the CCCF can both reduce vulnerability to climate risks and address tensions over scarce resources. Evidence from Kitui shows that inclusive governance structures, particularly Ward Climate Change Planning Teams (WCCPTs), have strengthened democratic decision-making, representation, and accountability while embedding conflict risks into adaptation planning. Projects such as the Kalikuvu earth dam illustrate how investments in water infrastructure can ease inter-community tensions and generate tangible peace dividends. Nonetheless, challenges remain. Cross-boundary planning is underdeveloped, funding flows are vulnerable to political cycles, procurement frameworks sometimes clash with community expectations, and monitoring systems inadequately capture peace outcomes. To sustain progress, the brief recommends enhancing transparency and funding consistency, building mechanisms for cross-county cooperation, expanding project sustainability, and systematically documenting peace and conflict dynamics. Kitui’s experience demonstrates the potential of devolved climate finance to act not only as a resilience tool but also as a platform for inclusive governance and peaceful coexistence.